Evolution of implants and advancements for osseointegration: A narrative review. (November 2022) - Walter, Nike; Stich, Theresia; Docheva, Denitsa; Alt, Volker; Rupp, Markus
Abstract: Since ancient times, reduction and internal fixation has been applied to restore skeletal integrity. Despite advances in the understanding of fracture healing, the risk of complication such as implant loosening or implant-related infection still depicts a challenging complication. Nowadays, a great deal of research is devoted to unreveal the impact of implant surface modifications on osteogenic processes to enhance bone consolidation and osseointegration. This narrative review is aimed to (1) show the evolution and already achieved milestones of implant optimization, and (2) to outline the key factors that contribute to an enhanced osseointegration. Different physical and chemical roughening techniques are currently applied in various studies. Surface patterning on the nanoscale has been found to be an essential factor for the biological response, achievable by e.g. anodisation or laser texturing. Besides surface roughening, also different coating methods are vastly investigated. Next to metal or inorganic compounds as coating material, a variety of biomolecules is currently studied for their osteosupportive capacities. Osseointegration can be improved by surface modification on the micro and nanoscale. Bioactive agents can further improve the osseointegration potential. Used agents at the moment are e.g. inorganic compounds, growth factors (BMPs and non-BMPs) and antiresorptive drugs. The advancement in research on new implant generations therefore aims at actively supporting osseointegration processing.